Gynecological acute abdomen - Herrera Calmet, Abelardo (2015)
The "Health Center" of Magdalena, cares for a sector of population of the Magdalena district, a part of the great Lima. The maternal mortality rate for the Magdalena district of 7 per 10,000 is low compared to that of great Lima 15.6 per 10,000. The study reported tries to gain insight as to the efficacy of the prenatal care program of the Health Center through a survey of a sample of the population covered by this service. It is concluded that the scope and type of service given to these mothers is adequate in regard to the prevention of major illness during pregnancy, delivery and puerperium but can not control the incidence of gynecologic complications that seems to be important to determinate te high rate (35.7%) neonatal mortality observed in the study.